Linking Asia's trade, logistics, and infrastructure - Douglas H. Brooks (Asian Development Bank Institute (ADBI), 2008)
Infrastructure services, from both hard and soft infrastructure, play a vital role in facilitating Asia's export-led growth by keeping the prices of delivered goods in export markets competitive. Efficient infrastructure services lower transaction costs, raise value added, and increase potential profitability while also increasing and expanding linkages to global supply chains and distribution networks for producers. Asia's trade patterns are characterized by a high degree of intraregional trade, particularly in parts and components for geographically fragmented production networks. This is both in response to, and with implications for, further infrastructure development. Logistics services play a key role and the challenges of providing efficient logistical support rise as countries move into progressively more complex and higher-value manufacturing, and as production processes become increasingly fragmented.
Keywords: F15; F13; O19; 330